2005
DOI: 10.1002/neu.20097
|View full text |Cite
|
Sign up to set email alerts
|

Expression of muscarinic acetylcholine receptors and choline acetyltransferase enzyme in cultured antennal sensory neurons and non-neural cells of the developing mothManduca sexta

Abstract: Antennal sensory neurons of Manduca sexta emerge from epidermal cells that also give rise to sheath cells surrounding the peripheral parts of the neurons and to glial cells that enwrap the sensory axons in the antennal nerve. Reciprocal interactions between sensory neurons and glial cells are believed to aid in axon growth and guidance, but the exact nature of these interactions is not known. We investigated the possibility of cholinergic interactions in this process by locating muscarinic acetylcholine recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Real-time quantitative RT-PCR analysis on the brains of three castes showed that PmAchR was expressed in all tested samples, which accords with previous studies revealing that mAchRs was expressed in various insect nervous systems (Blake et al, 1993;Torkkeli et al, 2005). The lowest expression level in the brains of males may relate to male biology: males have the simplest behavior in its short life: they leave the nest, fly, and mate with a female ant before they die.…”
Section: Discussionsupporting
confidence: 91%
“…Real-time quantitative RT-PCR analysis on the brains of three castes showed that PmAchR was expressed in all tested samples, which accords with previous studies revealing that mAchRs was expressed in various insect nervous systems (Blake et al, 1993;Torkkeli et al, 2005). The lowest expression level in the brains of males may relate to male biology: males have the simplest behavior in its short life: they leave the nest, fly, and mate with a female ant before they die.…”
Section: Discussionsupporting
confidence: 91%
“…This process necessarily involves detection of odor cues through receptors on the antennae and mouthparts. In other insects, and presumably in the honey bee, cholinergic projections carry these signals to the antennal lobes and the gustatory regions of the subesophageal ganglion [14,18,19,34,37]. Cholinergic projection neurons in turn convey information about chemical signals to the lateral horn and mushroom bodies of the protocerebrum [11,41].…”
Section: Nih Public Accessmentioning
confidence: 99%
“…A number of specific ChAT antibodies have made it possible to map immunohistochemically detailed cholinergic systems mainly in mammals (Kimura et al, 1980(Kimura et al, , 1981Eckenstein and Thoenen, 1982) and partly in some nonmammalian vertebrates, including birds (Johnson and Epstein, 1986;Medina and Reiner, 1994), amphibians (Marin et al, 1997), fishes (Tavares and Hasson-Voloch, 1998;Adrio et al, 2000;Anadón et al, 2000;Pérez et al, 2000;Pombal et al, 2001;Mueller et al, 2004), and lizards (Medina et al, 1993). In invertebrates a similar approach has been used to produce antibodies against purified ChAT from invertebrate animals, though limited to animals such as flies (Takagawa and Salvaterra, 1996;Yasuyama et al, 2003), moths (Clark et al, 2005;Torkkeli et al, 2005), and worms (Duerr et al, 2008). In addition, antibodies against human placenta ChAT have been applied to study crossreactive proteins in arthropods (Rind and Leitinger, 2000;Lipovsek et al, 2003) and crustacea (Faimali et al, 2003;Gallus et al, 2006).…”
mentioning
confidence: 99%